Pertanggungjawaban Pidana Illegal Minyak Dan Gas Bumi Oleh Nakhoda/Crew Kapal Dalam Sistem Peradilan Pidana Indonesia - Aditya Rezeki Ramadhan; Joko Sriwidodo; Kristiawanto Kristiawanto (Jurnal Penelitian Hukum Legalitas, 2021)
Business activities in the oil and gas sector that violate the laws and regulations in the oil and gas sector. Especially carried out by the captain / crew of tankers or other types of ships such as tugboats, cargo, SPOB and others. The research method is juridical-normative. The source of data in this study is secondary data. Data collection was carried out using field research, while the data analysis technique used was normative juridical analysis, making it possible to produce conclusions regarding criminal law enforcement and criminal liability in the oil and gas sector carried out by the captain/ship crew. Based on research that legal sanctions perpetrators of criminal acts in the field of Oil and Gas have not been able to make a major contribution in order to suppress or eliminate or hinder acts of law violations in the field of Oil and Gas, because there are still many legal loopholes from the Regulations and Legislation created by the Government. Therefore, the management of oil and gas must be improved comprehensively and thoroughly in one law and it is not sufficient if it is only partially regulated in the Job Creation Law so there needs to be a comprehensive overhaul of the new law